PROVERBIOGENÈSE ET OBSOLESCENCE: LA NAISSANCE ET LA MORT DES PROVERBES : LA NAISSANCE ET LA MORT DES PROVERBES - Villers, Damien (Proverbium - Yearbook, 2015)
This study deals with the birth and death of proverbs: how and why do they “come and go”? Some English and French proverb specimens will be studied in order to point out the different reasons why some sayings gain proverbial currency while others don’t, and on the other hand why some proverbs lose their currency and fall out of use while others last for centuries. This study will first include the description of the sources for many ancient or modern proverbs and the description of the criteria that boost or grant their status or ‘proverbialization’. This will call for an objective and scientific definition of the proverb that allows the classification and distinction of all sayings and idioms. This will make possible the description of the different steps of a very mysterious phenomenon – proverbial birth – which will be referred to as “proverbiogenesis”. Finally, a part will be devoted to the different ways proverbs can “die”, whether “naturally” or by genre shifting (mutation).